Bond strength of lap spliced steel bars in RC beams strengthened with low-cost natural FRP composites: Experimental and theoretical study - Hussain, Qudeer; Ruangrassamee, Anat; Ejaz, Ali; Jirawattanasomkul, Tidarut; Zhang, Dawei; Saingam, Panumas (My University, 2025)
Natural FRPs have proven their prospective in enhancing the compressive behavior of concrete. However, their effectiveness in preventing brittle steel lap splice failure has not been investigated. This study utilizes low-cost hemp and cotton eco-friendly ropes for the first time and proposes a bond strength-based model for its design. Twenty-six RC beams in three groups were tested, with varying lap splice lengths and layers of Natural Fiber Reinforced Polymers. The study reveals that Natural FRP effectively reduces concrete cover delamination and improves structural performance, while reinforced beams still exhibit noticeable cracks at lap splice ends upon failure. Notably, hemp and cotton configurations demonstrate effectiveness in enhancing load capacity, with hemp showing superior ductility restoration, especially for lap splices of 28db. The peak load and ultimate deflection (i.e., the deflection against a 20 % drop in peak load) improved between 17.6 % and 73.6 % and 36.9–837.2 % compared to the control beam without strengthening, respectively, with hemp confinement configuration Type B enhancing peak load by 73.6 % and 73.1 % for lap splice lengths of 20db and 28db, respectively. The inclusion of extra Natural FRP length on both sides of the lap splice appeared to impede vertical crack propagation, delaying beam failure. Furthermore, the paper addresses the challenge of predicting bond strength improvements under Natural FRP confinement due to the significant difference in elastic moduli between Natural FRP and synthetic FRPs. It proposes a strain-based approach to predict bond strength enhancements, yielding close agreement with experimental results, suggesting its potential in Natural FRP confinement design to prevent lap splice failures, albeit with consideration of lap splice properties matching those in the study.
Keywords: Bond strength; Cotton; Hemp; Lap splice; Natural fiber reinforced polymers; Reinforced concrete beams